1988
DOI: 10.1016/0031-9384(88)90259-4
|View full text |Cite
|
Sign up to set email alerts
|

Preference differences for sucrose solutions in young and aged squirrel monkeys

Abstract: INFORMATION TO USERSThis reproduction was made from a copy of a document sent to us for microfilming. While the most advanced technology has been used to photograph and reproduce this document, the quality of the reproduction is heavily dependent upon the quality of the material submitted.The following explanation of techniques is provided to help clarify markings or notations which may appear on this reproduction. 1. The sign or "target" for pages apparently lacking from the document photographed is "Missing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…We found that the lick rate during the first minute was significantly decreased in older rats, suggesting a decrease in the hedonic impact of sucrose and corn oil in old rats. However, given the failure to demonstrate such a deficit in the more specific tests for hedonic impact discussed above, the decrease could also be due to the age-related decline in orolingual motor performance observed; consistent with other reports in F344 rats (Stanford et al, 2003), and aged monkeys (Michels et al, 1988). Alterations in orolingual motor function including dysarthria, dysphagia, and masticatory deficits have been linked to morbidity and mortality in the elderly (Baum and Bodner, 1983; Lieu et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…We found that the lick rate during the first minute was significantly decreased in older rats, suggesting a decrease in the hedonic impact of sucrose and corn oil in old rats. However, given the failure to demonstrate such a deficit in the more specific tests for hedonic impact discussed above, the decrease could also be due to the age-related decline in orolingual motor performance observed; consistent with other reports in F344 rats (Stanford et al, 2003), and aged monkeys (Michels et al, 1988). Alterations in orolingual motor function including dysarthria, dysphagia, and masticatory deficits have been linked to morbidity and mortality in the elderly (Baum and Bodner, 1983; Lieu et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…The effects of concentrations of various carbohydrate solutions have been studied under several conditions, such as sham feeding (Davis & Smith, 1990, 1992), dopamine (DA) blocking (Gramling, Fowler, & Collins, 1984), and administration of putative satiety hormones (cholecystokinin and bombesin; Hsiao & Spencer, 1983). The behavioral adjustments for sucrose stimuli have been shown to be different between young and old squirrel monkeys (King, Hsiao, & Leeming, 1986; Michels, King, & Hsiao, 1988). Along with licking-response patterns, the force of tongue extension has been directly measured to study the effect of DA blocking with haloperidol (Fowler & Mortell, 1992).…”
mentioning
confidence: 99%